A Study On Effectiveness And Safety Use Of Antibiotics In Febrile Neutropenic Patients With Solid Tumor And Hematological Malignancies In King Fahad Specialist Hospital Saudi Arabia. - Rahaman, Sirkhazi Mansoor (2016)

(untitled)
Neutropenia adalah faktor pendorong bagi pesakit-pesakit kanser mengalami komplikasi dan jangkitan-jangkitan teruk terutamanya patogen-patogen gram negatif dan positif.